Characterization of Ba0.55Sr0.45TiO3 films as light and temperature sensors and its implementation on automatic drying system model. Issue 168 (2nd January 2016) - Irzaman,; Siskandar, Ridwan; Aminullah,; Irmansyah,; Alatas, Husin
Abstract: The growth of Ba0.55 Sr0.45 TiO3 films on p-type silicon substrate with depletion and enhancement treatments have been conducted in this research. The aims were to examine film sensitivity as light sensor and value range, resolution, acuracy level, and their hysteresis as temperature sensor. The films were annealed at 800, 850, and 900 °C for 15 hours. In this work, enhancement BST of 850 °C was the best quality film and utilized as light and temperature sensors. Its implementation has been successfully conducted on ATMega8535 microcontroller-based automatic drying system model by exploiting the working principle of the BST films as automatic switch.